2016
DOI: 10.1186/s12977-016-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of Vpu on the promotion of HIV-1 replication in the humanized mouse model

Abstract: BackgroundTetherin is an intrinsic anti-viral factor impairing the release of nascent HIV-1 particles from infected cells. Vpu, an HIV-1 accessory protein, antagonizes the anti-viral action of tetherin. Although previous studies using in vitro cell culture systems have revealed the molecular mechanisms of the anti-viral action of tetherin and the antagonizing action of Vpu against tetherin, it still remains unclear how Vpu affects the kinetics of HIV-1 replication in vivo.ResultsTo quantitatively assess the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…These observations suggest that HIV-1M is more optimally adapted to infect humans than the other viruses. Importantly, only HIV-1M Vpu potently antagonizes the antiviral action of human tetherin (29), and our experimental-mathematical analyses have recently shown that HIV-1M Vpu markedly increases the rate of viral replication in vivo (47). All together, these findings strongly suggest that the Vpu-tetherin interaction may be a critical step for increasing viral fitness in vivo.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These observations suggest that HIV-1M is more optimally adapted to infect humans than the other viruses. Importantly, only HIV-1M Vpu potently antagonizes the antiviral action of human tetherin (29), and our experimental-mathematical analyses have recently shown that HIV-1M Vpu markedly increases the rate of viral replication in vivo (47). All together, these findings strongly suggest that the Vpu-tetherin interaction may be a critical step for increasing viral fitness in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…5B and C). We have previously demonstrated that HIV-1M Vpu augments viral dissemination in our humanized-mouse model (39,47). To directly evaluate the effect of the antitetherin ability of Vpu on viral propagation in vivo, we prepared an SIVcpzPtt MB897 derivative that incorporates the transmembrane domain of HIV-1M (strain NL4-3) Vpu and is designated MB897 NLvpuTM, in accordance with a previous report (28).…”
Section: Resultsmentioning
confidence: 94%
“…To parameterise coronavirus infection dynamics from patient viral load data, we derived a simplified mathematical model from the following virus dynamics model: preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted March 27, 2020. ; https://doi.org/10.1101/2020.03.23.20040493 doi: medRxiv preprint the clearance rate of virus is typically much larger than the death rate of the infected 252 cells in vivo (10,19,20), we made a quasi-steady state (QSS) assumption, 253 ( )⁄ = 0 , and replaced Eq. 3 Accordingly, we obtained the following simplified mathematical model, which we employed to analyse the data in this study:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…To model COVID-19 dissemination among susceptible target cells, we used a mathematical 132 model previously proposed in 8 .…”
mentioning
confidence: 99%